Diagnostic Efficacy of HbA1c in Diagnosis of Diabetes Mellitus in a Bangladesh Population (Bangladesh Medical Journal, 2014)
American Diabetic Association (ADA) affirms HbA1c with cut off value of 6.5% as a diagnostic criteria of diabetes mellitus. World Health Organization (WHO) also supports but recommended that a value